UNDERSTANDING TEACHERS' MOTIVATION: PROFILES OF EARLY CHILDHOOD TEACHERS CONTINUING THEIR STUDIES - Aisyatin Kamila; Sa’diah, Halimatus; Hidayaturrochman, Rizki (Jurnal At-Taujih, 2024)
This study aims to examine and analyze the motivation of early childhood education (ECE) teachers in pursuing higher education. The research method employed is descriptive qualitative, involving students from semesters 1 to 7 who meet the criteria of being ECE teachers and continuing their studies in the PIAUD Department at Ibrahimy University Situbondo. Data collection was carried out using three methods: interviews, observations, and document studies. Subsequently, the researcher analyzed the collected data through three stages: data reduction, data presentation, and conclusion drawing. After conducting the research steps mentioned above, the researcher concluded that the dominant motivation for teachers to continue their studies is primarily driven by external factors, such as educational alignment, institutional demands, and improving their quality of life. Internal motivations include enhancing personal quality as educators and support from their families. Lastly, the university's easy learning system and affordable tuition fees also contribute as motivational factors. Keywords: Motivation, Learning, ECE Teachers